LESI OTAK FOKAL DENGAN PCR EBV CAIRAN SEREBROSPINAL POSITIF PADA PASIEN AIDS DI RS CIPTO MANGUNKUSUMO - Norma Mediciani*, Andini Aswar*, Riwanti Estiasari**, Nurul Komari**, Darma Imran** (Neurona Majalah Kedokteran Neuro Sains, 2012)
BACKGROUND FOCAL BRAIN LESIONS IN AIDS MAY BE CAUSED BY OPPORTUNISTIC INFECTIONS CEREBROVASCULAR DISEASE AND MALIGNANCY IN ADDITION TO TOXOPLASMA ENCEPHALITIS TE AND TUBERCULOMAS PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA PCNSL IS ONE OF THE ETIOLOGY OF FOCAL BRAIN LESIONS IN AIDS POSITIVE EXAMINATION OF POLYMERASE CHAIN REACTION PCR EPSTEIN BARR VIRUS IN CEREBROSPINAL FLUID FROM SOME STUDIES HAVE HIGH SPECIFICITY AND SENSITIVITY ALTHOUGH THE DEFINITE DIAGNOSIS PCNSL IS THROUGH BIOPSY